Between Ethnic and English Names: Name Choice for Transnational Chinese Students in a US Academic Community - Diao, Wenhao (Journal of International Students, 2014)
This article explores how transnational Chinese students negotiate identity options through name choice while studying in the US. Name choice can discursively index membership in various communities. Drawing on theories of heteroglossia (Bakhtin, 1981) and community of practices (Lave and Wenger, 1991), this study examines how name choice becomes a site of identity negotiation for transnational Chinese students who received their English names from ESL classes in China. Using a qualitative approach, the analysis illustrates divergent patterns in name choice among a group of transnational Chinese students within one academic community, and demonstrates how membership in the community intersects with notions of cosmopolitanism to affect their name choice. The findings shed light on the pedagogical practice of assigning English names in ESL classrooms. They also call for future research to study the complex links between Chinese students’ histories of engagement in such practices and their identity negotiation processes when overseas.